Conversion of Andean montane forests into plantations: Effects on soil characteristics, microorganisms, and microarthropods. (19th July 2020) - Marian, Franca; Ramírez Castillo, Pablo; Iñiguez Armijos, Carlos; Günter, Sven; Maraun, Mark; Scheu, Stefan
Abstract: Tropical montane forests in the Andes are subjected to deforestation and subsequent transformation into pastures. Abandoned pastures are frequently reforested by planting monoculture timber plantations, resulting in reduced aboveground diversity and changes in soil characteristics compared to primary forests. In this study, we evaluated differences in soil properties (litter layer thickness, pH, water content, and C‐to‐N ratio) between degraded primary montane forest and monoculture pine ( Pinus patula) and alder ( Alnus acuminata) plantations and their effects on density, diversity, and community structure of litter and soil‐living mesofauna, with focus on oribatid mites (Acariformes). The study was performed in a montane region in the southern Ecuadorian Andes (2, 000–2, 600 m a.s.l.). C‐to‐N ratios in the litter and upper 5 cm soil layer were higher in pine plantations, while other soil characteristics were similar between vegetation types. Surprisingly, microbial biomass and density of soil mesofauna in the litter layer did not differ between vegetation types, while density and species richness of oribatid mites were higher in pine plantations. Community structure of oribatid mites differed between vegetation types with only a few species overlapping. The results indicate that quality and diversity of litter were not the major factors regulating the mesofauna community. Instead, soil animals benefited from increased habitat structure in thicker litter layers and potentially increased availability of root‐derived resources. Overall, the results suggest that from a soil animal perspective, monoculture plantations are less detrimental than commonly assumed and enrichment of abandoned plantations with native tree species may help to restore tropical montane forests. Abstract in Spanish is available with online material. Resumen: Los bosques montanos tropicales son deforestados para la agricultura, principalmente pastizales. Los pastizales abandonados frecuentemente son reforestados con monocultivos de especies maderables, alterando las características del suelo, y la diversidad y estructura de la comunidad de microartrópodos. Se identificó diferencias en las propiedades del suelo (grosor de la capa orgánica, contenido de agua, y radio C/N) entre bosques montanos secundarios y plantaciones de pino ( Pinus patula ) y aliso ( Alnus acuminata ), evaluando sus efectos sobre la comunidad de mesofauna de la hojarasca y suelo, con énfasis en oribatid mites. El estudio se realizó alrededor de la ciudad de Loja al sur de los Andes ecuatorianos (2, 000–2, 600 m s.n.m.). Los radios de C/N fueron más elevados en pino, mientras que otras propiedades del suelo fueron similares entre los tipos de vegetación estudiados. Sorprendentemente, la biomasa microbiana y la densidad de mesofauna no difirieron entre tipos de vegetación, mientras que la densidad y diversidad de oribatid mites fueron más altas en pino. La estructura de la comunidad difirió entre tipos de vegetación con pocas especies solapadas. Los resultados indican que la calidad y diversidad de la hojarasca no regulan principalmente a la comunidad de mesofauna, sino que se benefician del extenso sistema de raíces del pino. El estudio sugiere que, desde una perspectiva de la fauna del suelo, las plantaciones son menos perjudiciales de lo que se supone y pueden usarse en forma combinada para restaurar la diversidad de mesofauna y las funciones que proporcionan en los bosques montanos tropicales.